Benefits of choir singing on complex auditory encoding in the aging brain: An ERP study. Issue 1 (21st May 2022) - Pentikäinen, Emmi; Kimppa, Lilli; Makkonen, Tommi; Putkonen, Mikko; Pitkäniemi, Anni; Salakka, Ilja; Paavilainen, Petri; Tervaniemi, Mari; Särkämö, Teppo
Abstract: Aging is accompanied by difficulties in auditory information processing, especially in more complex sound environments. Choir singing requires efficient processing of multiple sound features and could, therefore, mitigate the detrimental effects of aging on complex auditory encoding. We recorded auditory event‐related potentials during passive listening of sounds in healthy older adult (≥ 60 years) choir singers and nonsinger controls. We conducted a complex oddball condition involving encoding of abstract regularities in combinations of pitch and location features, as well as in two simple oddball conditions, in which only either the pitch or spatial location of the sounds was varied. We analyzed change‐related mismatch negativity (MMN) and obligatory P1 and N1 responses in each condition. In the complex condition, the choir singers showed a larger MMN than the controls, which also correlated with better performance in a verbal fluency test. In the simple pitch and location conditions, the choir singers had smaller N1 responses compared to the control subjects, whereas the MMN responses did not differ between groups. These results suggest that regular choir singing is associated both with more enhanced encoding of complex auditory regularities and more effective adaptation to simple sound features. Abstract : In the present study, we explored the role of regular choir singing on both simple and complex auditory encoding using an ERP experiment with three oddball conditions in healthy older adult (age ≥60 years) choir singers and non‐singer control subjects.